PENGARUH CURRENT RATIO DAN GROSS PROFIT MARGIN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN PT BUKIT ASAM TBK PERIODE 2013-2022 - Dwirahma, Noprizelia; Nari Ratih Permada, Dewi (Journal of Research and Publication Innovation, 2024)
This study aims to determine whether there is an influence of Current Ratio and Gross Profit Margin on Profit Growth at PT Bukit Asam Tbk for the period 2013- 2022. The research method used is a quantitative method with secondary data through the Financial Report of PT Bukit Asam Tbk for the period 2013-2022 from the website (www.ptba.com and www.idx.co.id). The analysis method used is multiple linear regression analysis, classical assumption test, f test (simultaneous), T test (partial) through IBM SPSS Statistics 26. Based on the results of the study, it can be concluded that partially the Current Ratio does not have a significant negative effect on profit growth with a value of |tcount -0.946 < ttable 2.365| with a significance of 0.376 <0.05, while Gross Profit Margin has a significant effect on profit growth with a value of |tcount 4.245 > ttable 2.365| with a significance of 0.004 <0.05. Simultaneously, Current Ratio and Gross Profit Margin have a significant effect on profit growth with a value of |fcount 9.814 > ftable 4.46| with a significance of 0.009 <0.05. The coefficient of determination value of this study is 0.662 or 66.2%, which means that the independent variable is influenced by the dependent variable, while the rest is influenced by other variables not examined in this study.